2018
DOI: 10.1002/smtd.201800323
|View full text |Cite
|
Sign up to set email alerts
|

Heteroatom‐Doped Carbon Materials: Synthesis, Mechanism, and Application for Sodium‐Ion Batteries

Abstract: the standard electrochemical potential of Na (2.71 V vs Na + /Na) is lower than that of Li (3.04 V vs Li + /Li), the successful academic and commercial experiences of LIBs can be referred by SIBs. Therefore, SIBs have been regarded as the most promising alternatives to LIBs. In the past few years, many novel materials have been developed and evaluated as electrode materials for SIBs. For instance, a number of transition metal oxides, transition metal sulfides and fluorides, polyanions, Prussian blue compounds,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
162
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 247 publications
(163 citation statements)
references
References 87 publications
(121 reference statements)
1
162
0
Order By: Relevance
“…Among these, BDC are superb host/active materials due to their large‐scale production, morphological diversity, and in situ doped heteroatoms. It is well known that the doping of various heteroatoms would introduce numerous active sites, increase defect amounts, enhance the electronic conductivity, and improve the chemical adsorption ability, which can enhance the reaction activities and electrochemical kinetics in energy storage and conversion devices …”
Section: Bacterium Organismsmentioning
confidence: 99%
See 2 more Smart Citations
“…Among these, BDC are superb host/active materials due to their large‐scale production, morphological diversity, and in situ doped heteroatoms. It is well known that the doping of various heteroatoms would introduce numerous active sites, increase defect amounts, enhance the electronic conductivity, and improve the chemical adsorption ability, which can enhance the reaction activities and electrochemical kinetics in energy storage and conversion devices …”
Section: Bacterium Organismsmentioning
confidence: 99%
“…It is well known that the doping of various heteroatoms would introduce numerous active sites, increase defect amounts, enhance the electronic conductivity, and improve the chemical adsorption ability, which can enhance the reaction activities and electrochemical kinetics in energy storage and conversion devices. [6,88] Recently, nitrogen doping is the most widely studied single doping method to enhance the electronic conductivity and reaction activity. Using S. aureus as raw materials, Wu et al [82] have successfully synthesized a round-shaped S. aureus-derived carbon (SDC) with nitrogen heteroatoms (Figure 2a) though direct heat treatment at the temperature of 800 °C.…”
Section: Bacteria-derived Carbonsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the 1990s, carbon-based materials have been widely employed as electrode materials in various energy storage and conversion devices, especially different types of rechargeable batteries, where graphite is the most widely used anode material for almost all commercial lithium-ion batteries until now [13]. Notably, these rechargeable batteries store charges by the Faraday reaction process and the corresponding electrochemical kinetics are relatively slow [14][15][16]. For example, carbon materials in any bulk form offer a limited population of active sites and require long ion diffusion pathways, leading to badly compromised reaction kinetics and poor performance.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14] Recent studies reported that doping of heteroatoms such as B, N, O, P and S in carbon gives rise to electrode performance of the carbon in SIBs because of a favorable change in adsorption energy of sodium ions upon the heteroatom-doping. [15][16][17] In general, synthetic routes for the multicomponent materials are more complex and challenging when the number of component elements is increased.…”
mentioning
confidence: 99%